The Role of Framing in Reframing Conflict: A Comparative Quantitative Content Analysis of American and European Television Coverage of the 2025 Iran-Israel War (The Peerian Journal, 2025)
During international conflicts, the media not only reflect reality, but actively construct it through framing. This research presents a quantitative content analysis, comparing television coverage of a hypothetical "Twelve-Day War" between Iran and Israel in June 2025 across American (CNN, Fox News) and European (BBC France 24, DW) networks. Using Johan Galtung's "War/Peace Journalism" model as the primary analytical framework, this research aims to measure systematic differences in framing, source attribution, and portrayal of the warring parties. The research hypothesized that American networks, operating within a partisan business model, would exhibit greater variation in coverage aligned with domestic political divisions, while European public service broadcasters would adopt a more homogeneous "diplomatic frame" reflecting their countries' foreign policy positions. To test this hypothesis, a sample of (N ≈ 350) news clips broadcast during the conflict period was analyzed using a detailed coding scheme, with inter-coder reliability tests and statistical analysis (chi-square tests and analysis of variance) conducted to identify statistically significant differences in coverage variables. The results revealed a general dominance of war journalism, but with significant differences in the degree and type of bias between the American and European media context